NOVEL APPROACH TO ACUTE VIRAL RHINITIS TREATMENT IN CHILDREN - M.P. Emel'yanova; E.P. Karpova; D.A. Tulupov ("Paediatrician" Publishers LLC, 2011)
Acute viral rhinitis is one of the most frequent reasons for the administration of drugs in pediatrics. Complex treatment of acute rhinitis with isotonic solution of sterile oceanic water (Marimer) and nasal oxymetazoline results in shortening the duration of clinical symptoms of rhinitis.Key words: children, acute respiratory viral infection, rhinitis, oxymetazoline, irrigation therapy.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 115-118)